Early Childhood Education Figure in Indonesia - Istifarriana, Deva Mega (Islamic Studies Journal, 2023)
This research examines early childhood education leaders in Indonesia. The purpose of this study was to find out the biographies and thoughts of early childhood education leaders in Indonesia about early childhood education. This type of research is descriptive qualitative with a textual analysis approach or library research in the form of literature review. Source of data from several research books, journals, and other references. Data collection using documentation. Data analysis was carried out using several methods, namely data reduction, data classification, and verification of data information. The results of the study found and identified the thoughts of figures in Indonesia regarding early childhood education, including: 1) Ki Hajar Dewantara stated that the characteristics of early childhood education are character and the system among; 2) Ratna Megawangi states that there are 9 pillars of character that are important to instill in children; 3) Munif Chatib stated 7 new paradigms in early childhood care. From here, the thoughts and discoveries of figures in Indonesia regarding early childhood education can become our reference in assisting and educating early childhood